2020
DOI: 10.1111/bph.15206
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory drugs, prostaglandins, and COVID‐19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the novel coronavirus disease 2019 (COVID-19), a highly pathogenic and sometimes fatal respiratory disease responsible for the current 2020 global pandemic. Presently, there remains no effective vaccine or efficient treatment strategies against COVID-19. Non-steroidal anti-inflammatory drugs (NSAIDs) are medicines very widely used to alleviate fever, pain, and inflammation (common symptoms of COVID-19 patients) through effectively blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 253 publications
(410 reference statements)
2
73
1
4
Order By: Relevance
“…The high incidence of thromboembolic events from autopsy findings suggests an important role of COVID-19–induced coagulopathy [ 91 , 92 , 93 , 94 ]. In addition to the main strategies such as targeting SARS-CoV-2 attachment and entry to human and viral replication or systemic immune responses, targeting hyper-inflammation with steroids, such as dexamethasone and non-steroidal anti-inflammatory drugs (NSAIDs) have been attempted in a number of clinical trials [ 95 ]. Among NSAIDs, the anti-platelet drug, aspirin is significantly associated with reduced risk of developing COVID-19 certainly due to anti-inflammatory and anti-coagulant effects [ 95 ].…”
Section: Proposed Mechanisms For the Role Of Nets Formation In Covmentioning
confidence: 99%
See 1 more Smart Citation
“…The high incidence of thromboembolic events from autopsy findings suggests an important role of COVID-19–induced coagulopathy [ 91 , 92 , 93 , 94 ]. In addition to the main strategies such as targeting SARS-CoV-2 attachment and entry to human and viral replication or systemic immune responses, targeting hyper-inflammation with steroids, such as dexamethasone and non-steroidal anti-inflammatory drugs (NSAIDs) have been attempted in a number of clinical trials [ 95 ]. Among NSAIDs, the anti-platelet drug, aspirin is significantly associated with reduced risk of developing COVID-19 certainly due to anti-inflammatory and anti-coagulant effects [ 95 ].…”
Section: Proposed Mechanisms For the Role Of Nets Formation In Covmentioning
confidence: 99%
“…In addition to the main strategies such as targeting SARS-CoV-2 attachment and entry to human and viral replication or systemic immune responses, targeting hyper-inflammation with steroids, such as dexamethasone and non-steroidal anti-inflammatory drugs (NSAIDs) have been attempted in a number of clinical trials [ 95 ]. Among NSAIDs, the anti-platelet drug, aspirin is significantly associated with reduced risk of developing COVID-19 certainly due to anti-inflammatory and anti-coagulant effects [ 95 ]. Thus, we speculate that aspirin may reduce NETs induced immuno-thrombotic events, and that observation of NETs formation in the course of COVID-19 clinical trials involving aspirin administration that are ongoing, would be of interest.…”
Section: Proposed Mechanisms For the Role Of Nets Formation In Covmentioning
confidence: 99%
“…The WHO has indicated that there is no evidence to confirm an aggravation of COVID-19 infection with the administration of NSAIDs [30,31]. In fact, it has been reported that some NSAIDs could have some type of activity against viruses such as VZV [32], HCMV [32], HSV-1 [33], influenza virus A⁄ H1N1 subtype [34,35], VSV [36,37], EBOLA [38,39], HIV [40], JEV [41], CHIKV [42], SARS-CoV-1 [43], and recently against SARS-CoV-2 [35,44,45]. Additionally, many studies have been carried out that propose various targets for blocking virus recognition, importation and replication processes through the use of reused drugs, immunotherapies, interference strategies and various inhibitory compounds [46].…”
Section: Introductionmentioning
confidence: 99%
“…Grapiprant is an anti-inflammatory prostaglandin inhibitor currently used to treat inflammatory pain by competitively inhibiting the prostaglandin E 2 (PGE 2 ) receptor protein subtype 4 (EP4) ( Nakao et al, 2007 ). EP4 is abundantly expressed on the surface of lung cells and almost all immune cells ( Robb et al, 2020 ). After PGE 2 -binging, EP4 can initiate a wide range of physiological effects including cellular differentiation, proliferation, angiogenesis, and inflammation ( Kalinski, 2012 , Konya et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%